Awareness of smart home interior in Malaysia: a systematic review - Awang, Arita Hanim; Halim, Nor Hafiza; Ab Jalil, Nurlelawati; Ab Rahman, Syakir Amir; Hj. Mohd. Noor, Norzailawati; Sapian, Abdul Razak; Ahmad, Norfazillah (IIUM Academy of Graduate and Professional Studies, Kuala Lumpur, Malaysia., 2025)
Home has always been a place of relaxation, refuge, and sanctuary offering relief from the world's busyness and intrusiveness. As the home becomes an important place for all as their place of rest, a smart home has been introduced as a place full of functionality. In the past, smart homes were considered part of a lavish lifestyle but have become an integral part of our lives today. But nowadays, it has become dominant as it is important in creating comfort, energy-saving, security, and efficiency. In this paper, the study will focus on the level of awareness regarding the smart home in Malaysia by using a systematic review. The systematic review presents an overview of ideas to specifically address and enable one or more designated research questions in the availability of potentially relevant studies. For accurate papers in an electronic search engine, it requires proper evaluation of the databases and keywords.